GAYA HIDUP KELUARGA BERPERILAKU MENYIMPANG DI PEKANBARU - Ermairel S (LPPM STISIP Persada Bunda, 2022)
The research was carried out in Sidomulyo Housing RT. 02 RW. 01 Village Maharatu, Marpoyan Damai District, Pekanbaru. The purpose of this research is to knowing the life Style of family members who behave deviantly, to fine out the cause of deviant behavior and to find out the importance of inculcating good values and norms in the family. Benefits of research this is to make new knowledge in communication science that education values and norms in the family are very important. Become of referencefor researchers and observers of deviant behavior and make new study in the world of communication. Understanding can prevent deviant behavior in socienty. The implementation time of this research starts from April to June 2021. Data collection techniques with observation, interviews and dokumentation. Technique data analysis with qualitative analysis. From the results of the study it was found that the style of life (Life Style) must be adapted to the family economy, in the family it is necessary instilled basic moral values such as religion and shame in order to avoid behavior deviant, and a lazy lifestyle makes the family economy low. It is expected that parents and family members shoud have a lifestyle adjusted to economic capacity. To compete in the midst of urban progress we must have adequate education and skills. very good communication needed in a family. A very good father/family head fiqure determine so that family members avoid deviant behavior